Peranan Guru Bimbingan Konseling (BK) dalam Menyelesaikan Masalah Untuk Meningkatkan Hasil Belajar Peserta Didik - fauzi, agusta; zulyusri, zulyusri (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2023)
Counseling Guidance (BK) is a program that provides direction and motivation in learning and assists students in solving existing problems. The role of Counseling Guidance (BK) is also the right solution according to the problems faced by students. The purpose of this research is to observe the role of Counseling Guidance Teachers (BK) in solving problems so that students' enthusiasm for learning increases. The results of this study by providing appropriate services and guidance, students are able to overcome their problems and are more motivated to learn. In this study the method used is a systematic review. The data used in this research is secondary data. Data taken from several sources such as articles or journals, both national and international, which have been carried out by previous researchers. Search for articles and journals using the database on Google Scholar or other references with the keyword The role of the guidance and counseling teacher (BK) to complete student problems.